Kontrol Diri Perempuan Dewasa Awal Penggemar K-Pop Terhadap Perilaku Celebrity Worship - Citra; Ratna Yunita Setiyani Subardjo (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study was conducted with the aim of finding out the relationship between self-control and celebrity worship in early adult women who are K-Pop fans. Korean popular music culture, or better known as 'K-pop' has become a phenomenon that is able to attract many fans or what is also commonly called 'fans' or fans from all over the world, including Indonesia. Contrary to the perception that develops in society, the behavior of K-Pop fans in expressing love for idols is often considered excessive and considered too extreme, so that K-Pop fans are often considered obsessive, possessive, and even delusional. The higher the level of addiction to a person to a celebrity, the higher the level of a person's worship and the higher the level of involvement with the idol. The absence of self-control will cause individual difficulties in thinking about the impact of all behaviors that have been done. This study uses a quantitative approach and the determination of the sample of this study uses a purposive sampling technique. The sample used in this study was 200 people taken from the female population aged 20-30 years and K-Pop fans in Yoyakarta with the number of samples considered to be representative of the existing population. The population in this study is women aged 20-30 years and K-Pop fans in Yoyakarta. Based on the analysis of the hypothesis test carried out, it was shown that the significant value of P = 0.029 > 0.05, the result was obtained that there was no negative relationship between self-control and celebrity worship behavior and it is known that the R Square value is 0.003 or equal to 3% so that it can be interpreted that the independent variable, namely celebrity worship, affects the bound variable, namely self-control with the possibility that it occurs only 3% because it is influenced by other factors.